Natural Disaster Management Knowledge and Practices of the Rural Communities in Bangladesh - Koli, Kamrunnahar; Begum, Salma; Hossain, Md Shakhawat; Rahisul Islam, Md (South Asian Journal of Social Sciences and Humanities, 2025)
This study aims to assess disaster management knowledge and practices among rural residents in four communities of Pabna and Sirajganj Districts, Bangladesh. A survey of 180 households was conducted to collect data. Respondents were randomly selected for interviews without regard to religion or ethnicity. Multistage sampling identified respondents using a structured questionnaire for data collection. Six key informant interviews (KII) were conducted to gather qualitative data. Participants included local social elites, religious leaders, government agencies, and NGOs. Eight case study methods were employed to gather data on natural disasters over time. Each FGD session involved eight to twelve attentive respondents with comparable backgrounds who shared their opinions. The emphasis was on acquiring factual and valuable information verified against other sources. Facilitators employed a discussion guide and documented the proceedings. Data entry was conducted using MS Access, while SPSS-20 was employed for data tabulation. The study indicated notable enhancements in individuals’ knowledge, practices, and awareness regarding disaster preparedness, including food preservation, financial savings, secure document storage, and awareness of nearby safe shelters. The study indicated notable enhancements in disaster preparedness, early warning systems, coping strategies, and health and hygiene practices. 98.3% of respondents received early warning messages during floods, whereas only 25% did so. Neighbours and family members were the primary sources of early flood warnings. Research shows that communication media is essential in managing natural disasters. The government should implement initiatives to enhance community awareness of natural disasters and offer disaster preparedness training.